SINTESIS, KARAKTERISASI, DAN UJI AKTIFITAS FOTOKATALITIK NANOPARTIKEL MAGNETIK TiO2-CoFe2O4 - -, Rahmayeni,; Septiani, Upita; Arief, Syukri; Hamdi, Hayatul (Universitas Andalas, 2011)
ABSTRACT Magnetic nanoparticles of TiO2−CoFe2O4 were prepared using metal nitric and tiatniumisopropoxide as starting materials by coprecipitation and hydrolysis method. XRD, SEM, EDX and VSM were used to characterize the structure, morphology, composition and magnetic property of the particles, respectively. XRD pattern show the diffraction peaks of TiO2 anatase at 2θ = 25.3° and CoFe2O4 at 2θ = 35.5° in TiO2−CoFe2O4 particles. SEM image show the regular morphology and size distribution of particles. From VSM analysis indicate that the particles have paramagnetic properties. Photocatalytic activities of particles were applied for degradation of rhodamin B and the results showed that CoFe2O4 doped into TiO2 can increase the activities of particles in visible light until 82 %. Key words : nanopartikel magnetik, TiO2−CoFe2O4, fotokatalis